Characterization of PRRSV in clinical samples and the corresponding cell culture isolates. Issue 5 (26th July 2022) - Yim‐im, Wannarat; Huang, Haiyan; Zheng, Ying; Li, Ganwu; Rawal, Gaurav; Gauger, Phillip; Krueger, Karen; Main, Rodger; Zhang, Jianqiang
Abstract: Isolation of porcine reproductive and respiratory syndrome virus (PRRSV) in cell culture is a primary means of obtaining virus isolates for autogenous vaccine production and other applications. However, it has not been well characterized whether cell culture isolate and the virus in clinical sample are equivalent. This study compared PRRSV ORF5 sequences from 1024 clinical samples (995 PRRSV‐2, 26 PRRSV‐1, and three PRRSV‐1 and PRRSV‐2 PCR‐positive) and their isolates in MARC‐145 and/or ZMAC cells. For three PRRSV‐1 and PRRSV‐2 PCR‐positive clinical samples, both PRRSV‐1 and PRRSV‐2 were isolated in ZMAC cells, whereas either PRRSV‐1 or PRRSV‐2, but not both, was isolated in MARC‐145 cells, with isolate sequences matching the respective viruses in clinical samples. Twenty‐six PRRSV‐1 and most of 995 PRRSV‐2 PCR‐positive clinical samples had matching viral ORF5 sequences with their cell culture isolates. However, 14 out of 995 PRRSV‐2 cases (1.4%) had nonmatching viral sequences between clinical samples and MARC‐145 isolates, although viral sequences from clinical samples and ZMAC isolates matched. This is concerning because, if the MARC‐145 isolate is directly used for autogenous vaccine production without sequencing confirmation against the virus in the clinical sample, it is possible that the produced autogenous vaccine does not include the desired wild‐type virus strain found on the farm and instead contains vaccine‐like virus. Vaccine‐specific PCR and next‐generation sequencing performed on six selected cases indicated presence of ≥2 PRRSV‐2 strains (mixed infection) in such clinical samples. In summary, PRRSV ORF5 sequences from clinical samples and cell culture isolates matched each other for majority of the cases. However, PRRSV sequences between clinical sample and MARC‐145 cell culture isolate could occasionally be different when the clinical sample contains ≥2 PRRSV‐2 strains. Characterizing PRRSV sequences from clinical samples and cell culture isolates should be conducted before using isolates for producing autogenous vaccines or other applications.